The Introduction of Pedagogy of Pragmatism in the National System of Social Education of Juvenile Offenders in the Early 20’s of the Twentieth Century - Plisko, Yevgen (Pedagogical Discourse, 2018)
The similarity of the social, political and economic conditions in Ukraine and America in 20-30 years of the last century has prompted local educators to refer to the new ideas of education acquired popularity in the United States. It is based on the philosophy of pragmatism. The attention of local teachers to the American educational experience was caused by the presence of new ideas that were adequate to the tasks of social education in our country. The purpose of the study is a retrospective analysis of the formation of the pragmatic ideas of social and pedagogical education of juvenile offenders in a new stage of development of national pedagogy. Research methods. Analysis of the historical literature on the chosen research topic. Results. In the stage of formation of the system of social education of juvenile offenders is beholden to the influence of John Dewey, whose views formed the alternative in the domestic pedagogical space of social education of the stage research of the 20 – 30-ies of the last century. At this time, there are attempts to analyze the theoretical provisions of the pragmatic ideas of education, the investigation of the experience of introduction into practice, in the education of juvenile offenders of a dalton plan, project system, research method, comprehensive development of educational material. This was the reason that the impact of Western pedagogy in the domestic pedagogical thought and the system of social and pedagogical education of young people weakened. Among the borrowed ideas in the pedagogy of pragmatism and social education of juvenile offenders included: strengthening the connection of specialized institutions for difficult children with accommodation and production, development of individual abilities and aptitudes of pupils, formation of skills to plan their academic work, the system of control and self-control of education, training, based on the application of research method. Regarding the concept of education of juvenile offenders in the pragmatic model, its essence lies in the fact that all children committed offences handled by them in the form of their own independent research. Hard-to-learn children develop their own learning environment, plan certain life questions, analyze their mistakes, set goals to correct them, make a plan and path to address them. That was consistent with the main goal of national pedagogy in the early 20-ies of XX century – re-education into a fully developed, independent person.